From Vision to Impact; A Strategic Model to Improve Student Quality and Competence through Adaptive Educational Practices - Didik Wahyudi; Umar Manshur (Journal of Research in Educational Management, 2025)
The focus of this study is to analyze the principal's leadership strategy in improving the quality and competence of students at SMK Al Khairiyah, related to leadership practices and their impact on the formation of an educational environment. This study aims to analyze the principal's leadership strategy in improving the quality and competence of students at SMK Al Khairiyah. Using a qualitative approach, data were collected through in-depth interviews with the principal, teachers, and students, as well as analysis of related documents. Through the Miles and Huberman approach, data were analyzed to identify strategies implemented by the principal and their impact on the quality of education. The results of the study indicate that the principal has successfully integrated educational leadership theories, such as transformational leadership, into practice. Strategies such as curriculum development that is relevant to industry needs, intensive teacher training, and community involvement have contributed significantly to improving the quality and competence of students. The implications of this study highlight the importance of visionary and adaptive leadership in creating an educational environment oriented towards Islamic values, as well as providing guidance for Islamic education practitioners in designing effective leadership strategies to achieve broader educational goals. The implication of this study is the importance of the principal's visionary leadership in designing adaptive and effective educational strategies to improve the quality and competence of students, especially in the context of Islamic education.